BOND SECURING MECHANISM WITH REVIEW OF STATE IN REPUBLIC OF SERBIA - Krstić, Nikola B (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
In order to increase chances for bond emission success, and to achieve lower emission interest rates, bonds collateral is used. Established collateral can be personal or given on property. Personal type of collateral can be given as personal, bank or state guarantee as well as claim insurance, while property collateral could be given in form of pledge or mortgage. This paper is concerning practical issues that are specific for establishing each type of bond collateral, preconditions that must be fulfilled in order to establish certain types of collateral and well as question, weather is it possible to establish bond collateralization in Republic of Serbia.